Exploring Microfinance Clients with Disabilities: A Case Study of an Ecuadorian Microbank - Leif Atle Beisland; Roy Mersland (The Journal of Development Studies, 2017)
Using a unique sample from an Ecuadorian microfinance institution that has focused on increasing its outreach to disabled clients, we present a comparative analysis of the characteristics of disabled versus non-disabled clients. The study shows that disabled clients are more often male, are less likely to be living with a partner, have fewer children, and are older compared to their non-disabled counterparts. Moreover, we observe differences in repayment statistics between clients with and without disabilities, as well as differences within the disability sample. Our findings illustrate the importance of adapting microloans to the special needs of persons with disabilities.
Keywords: 650